NOTES ON DISTRIBUTION, BIOLOGY AND ECOLOGY OF PARACLYTUS SEXGUTTATUS (COLEOPTERA, CERAMBYCIDAE) - Georgiev, Georgi (Fragmenta entomologica, 2008)
Distribution of Paraclytus sexguttatus (adams, 1817) is analyzed in connection with establishment of localities in Bulgaria and Turkey. It is regarded as South-Pontian species with dispersal center Caucasus. Main biological and ecological characteristics of the species are given.